OPTIMIZATION COMMUNITY PROGRESS THROUGH EMPOWERMENT IN THE FIELD OF SUSTAINABLE EDUCATION - Suryanti, Suryanti; Rofiah, Chusnul; Asfahani, Asfahani; Cindy, Agustin Hanivia; Palayukan, Hersiyati (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
This service focuses on Optimizing Community Progress through Empowerment in the Field of Sustainable Education. The background of this article emphasizes the need for holistic global education that integrates environmental, social, and economic aspects. This service aims to empower the community to actively participate in sustainable education initiatives actively, fostering a sense of ownership, collaboration, and long-term impact. This service method uses participatory approaches such as Participatory Action Research (PAR) and Asset-Based Community Development (ABCD), emphasizing collaboration between stakeholders, including government agencies, NGOs, educational institutions, and community members. The results show significant increases in community ownership, participation, and commitment to continuing education programs. A participatory approach facilitates designing contextually relevant solutions and identifying locally relevant problems and opportunities. Asset-Based Community Development utilizes existing community strengths and resources for educational support, increasing independence and resilience. The conclusion is that community empowerment and collaborative partnerships are important in optimizing community progress in sustainable education. Empowered communities drive positive change, address local challenges effectively, and contribute to a more equitable and sustainable future. Collaborative partnerships ensure sustainable education initiatives' scalability, impact, and long-term sustainability and foster empowered communities.